Factors Emphasizing Ecological Influence on the Academic Performance of Educational Personnel in Nakhon Si Thammarat Primary Educational Service Area Office 3: Factors Emphasizing Ecological Influence on the Academic Performance of Educational Personnel in Nakhon Si Thammarat Primary Educational Service Area Office 3 - Chaiyadej, Phattharanat; Kumhom, Naitawan (RATANABUTH JOURNAL, 2025)
This research aimed to 1) examine the level of prioritization given to ecological influence factors, 2) assess the level of academic competency, and 3) investigate the relationship between the prioritization of ecological influence factors and the academic competency of educational personnel under the Nakhon Si Thammarat Primary Educational Service Area Office 3. The sample consisted of 385 educational personnel, determined using Krejcie & Morgan’s sample size table. The research instrument used was a questionnaire. Data were analyzed using mean, standard deviation, and Pearson’s correlation coefficient. The findings revealed that 1) The overall prioritization of ecological influence factors was at a relatively high level. When examined by dimension, the highest priority was given to individual factors, followed by organizational factors, and lastly, network factors 2) The overall academic competency was at a relatively high level. When categorized by dimension, self-development in academic work ranked first, followed by the pursuit and application of academic knowledge, and lastly, teamwork in academic work 3) The relationship between the prioritization of ecological influence factors and the academic competency of educational personnel, analyzed through multiple regression, showed that network, organizational, and individual factors yielded a multiple correlation coefficient (R) of 0.910. These factors significantly explained 82.80% of the variance in academic competency at the 0.01 statistical significance level (R² = 0.828). Hypothesis testing confirmed a statistically significant relationship between prioritized ecological influence factors and academic competency at the 0.01 level.